2021
DOI: 10.1039/d1fo01446c
|View full text |Cite
|
Sign up to set email alerts
|

Oat β-glucan alleviates DSS-induced colitisviaregulating gut microbiota metabolism in mice

Abstract: Oat β-glucan supplementation ameliorated DSS-induced colitis concurrently through regulating gut-derived SCFAs and intestinal microbial metabolic profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…In addition, increased consumption of coarse cereals containing dietary fiber contributes to healthy functioning of the intestine. Oat β-glucan mitigated the inflammatory status in colon, enhanced colonic barrier function, and increased gut microbiota-derived SCFAs (butyrate) in vivo [46,47]. Tartary buckwheat-resistant starch improved intestinal health by regulating the gut microbiota composition and increasing the yield of SCFAs in HFD fed mice [48].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, increased consumption of coarse cereals containing dietary fiber contributes to healthy functioning of the intestine. Oat β-glucan mitigated the inflammatory status in colon, enhanced colonic barrier function, and increased gut microbiota-derived SCFAs (butyrate) in vivo [46,47]. Tartary buckwheat-resistant starch improved intestinal health by regulating the gut microbiota composition and increasing the yield of SCFAs in HFD fed mice [48].…”
Section: Discussionmentioning
confidence: 98%
“…There is increasing evidence that the gut microbiota and their catabolites are closely related to gut health [ 41 ]. The composition and structure of the gut microbiota alters in the dysfunctional gut barrier, for example, the abundance of Firmicutes increased and the abundance of Bacteroidetes decreased in intestinal inflammation [ 42 ]. A recent study found that β-glucan improved gut barrier by decreasing the Firmicutes/Bacteroidetes ratio [ 42 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The composition and structure of the gut microbiota alters in the dysfunctional gut barrier, for example, the abundance of Firmicutes increased and the abundance of Bacteroidetes decreased in intestinal inflammation [ 42 ]. A recent study found that β-glucan improved gut barrier by decreasing the Firmicutes/Bacteroidetes ratio [ 42 ], which is consistent with our findings. In addition, we found that β-glucan increased the abundances of Bacteroides , Alloprevotella , Fournierella , Alistipes , and Oscillospira and decreased the abundance of Ruminococcaceae_NK4A214 in feces of the dairy calves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of whole-grain components on regulating the gut microbiota is summarized in Table 1. For instance, intake of oat β-glucan significantly ameliorated the clinical features of ulcerative colitis in mice, attenuating the severe colonic inflammatory status and improving colonic mucosal barrier function concurrently with regulating gut-derived SCFAs and intestinal microbial metabolic profiles [24]. According to the authors, the reversed expression levels of zonula occludens-1 (ZO-1), occludin, claudin-1, and claudin-4 indicated that oat β-glucan promoted tight junction protein formation and restored intestinal epithelial barrier function.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%